PENGEMBANGAN MEDIA PEMBELAJARAN “KARTU NUSANTARA” PADA MATERI KERAGAMAN SUKU BANGSA KELAS IV SDN REJOAGUNG 3 NGORO JOMBANG - Adila, Salsabela Nur; Fitra Raharja, Hawwin; Rizqi Salamah, Evi (Prodi Pendidikan Guru Sekolah Dasar, 2024)
This research is a typeof development research using the ADDIE model which includes Analysis, Design, Development, Implementation, Evaluation. This model is used to solve the problem of developing the